Resensi Hukum Syarak Terhadap Status Harta Syubhah Menurut Ulamak Shafi`iyyah: Sharia Law Review on the Status of Shubhah's Property According to Shafi'iyyah Ulamak - Mohamad Hilmi, Ahmad Misbah; Ibrahim, Mohamad Rofaizal; Abdullah, Mohamad Ismail; Ahmad, Khairul Anuar (Al-Basirah Journal, 2021)
This study is a literature review (Library Research). The sources of this study are the books of fiqh al-Shafi`iyyah, usul fiqh, and al-Qawaid al-Fiqhiyah related to the topic of study, which is doubtful wealth (Harta Syubhah). Some believe that doubtful wealth is not included in the wealth that is obligatory to be given as zakat, because Allah SWT only accepts from lawful and good sources. This issue stems from a shallow understanding of the true nature of the mixture between halal and haram, which gives rise to doubt. Furthermore, it is exacerbated by subjective interpretations of textual religious sources without reference to clear and objective legal methodologies in Islamic law. Therefore, this writing aims to address the implications of purifying Islamic law regarding doubtful property issues. It can serve as evidence in purifying Islamic law or be accepted as a legal principle in Islam. For this purpose, descriptive methods and content analysis are used in this study. The results of this study indicate that purifying Islamic law is crucial, especially concerning the status of doubtful property.